School maladjustment of immigrants: the self- concept neglected in the Psychology and Education studies of PISA series - Figueiredo, , Sandra (International Journal of Psychosocial Rehabilitation, 2020)
The last generation of immigrants has revealed different indicators in academic and cognitive performance in recent years. In different editions, the Organization for Economic Cooperation and Development (OECD) has evaluated the achievement of young students (aged 15 years old) in different academic areas (such as Sciences and Reading) as well as the performance of the first and second generation of immigrants. The immigrants were revealed to have fragile positions in school performance and negative indicators for their professional future by comparing to the native peers. Based on the PISA’s most recent edition (OECD, 2016), regarding the Portugal’s database of 438 immigrant cases, we examined background characteristics - length of residence (LOR) and type of generation (first or second) - as well as concerning inclusion and self-concept aspects that are measured using PISA items such as the School Adjustment. We intend to test the effect of the length of exposure in school adjustment of young immigrant students. We had followed the statistical analysis protocol determined by the PISA by means of sampling weights and plausible values using the IDB Analyzer. Students with low length of residence have more tendency to the maladjustment. However, other groups, especially those with periods of long-term residence between four and five years, also face substantial levels of school maladjustment. These data are important to understand the efficiency measures to be implemented in Portuguese schools, with replication in other European and non-European contexts, in order to reduce the stress indices in immigrant students and to avoid compromising their academic and economic future in the host countries.